INTERPERSONAL COMMUNICATION SKILLS ON STUDENT DISCIPLINE: ANALYSIS OF THE EFFECTS OF ISLAMIC RELIGIOUS LEARNING - Amin, Alfauzan; Alimni, Alimni; Kurniawan, Dwi Agus; Triani, Elza; Septi, Sabila Eka (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
The urgency of the research is that teachers can improve students’ interpersonal communication skills, which can affect student discipline in learning, so that their learning outcomes can be increased during the pandemic. The purpose of the study was to determine differences in teacher interpersonal communication skills and to determine student learning discipline distinctions in each school in Islamic education lessons, as well as the effect of teacher interpersonal communication skills on students' discipline during the COVID-19 pandemic at SMPN 20 Jambi City and SMPN 20 Bengkulu. The type of research is mixed methods with an explanatory design. The total number of samples was 72 active students with random sampling data collection techniques and data analysis techniques using descriptive and inferential statistics. The result of the T-test showed significant differences in teachers' interpersonal communication skills and distinctions in students’ learning disciplines in each school. Meanwhile, the regression test result indicated a significant influence of teacher interpersonal communication on student learning discipline in Islamic education lessons during the COVID-19 pandemic. Abstrak: Urgensi penelitian adalah guru dapat meningkatkan kemampuan komunikasi interpersonal kepada siswa yang dapat mempengaruhi kedisiplinannya dalam belajar, sehingga hasil belajarnya dapat meningkat di masa pandemi. Tujuan penelitian untuk mengetahui perbedaan keterampilan komunikasi interpersonal guru dan untuk mengetahui perbedaan disiplin belajar siswa pada masing-masing sekolah pada pelajaran pendidikan agama islam, serta untuk mengetahui pengaruh keterampilan komunikasi interpersonal guru terhadap disiplin siswa pada masa pandemi COVID-19 di SMPN 20 Jambi city dan SMPN 20 Bengkulu. Jenis penelitian yang digunakan adalah mix method research dengan explanatory design. Jumlah sampel 72 siswa aktif dengan teknik pengumpulan data random sampling dan teknik analisis data menggunakan statistik deskriptif dan inferensial. Hasil Uji-t menunjukkan bahwa terdapat perbedaan yang signifikan keterampilan komunikasi interpersonal guru di masing-masing sekolah serta disiplin belajar siswa, terdapat perbedaan di setiap sekolah. Hasil uji regresi menunjukkan bahwa terdapat pengaruh yang signifikan antara komunikasi interpersonal guru terhadap disiplin belajar siswa pada pembelajaran pendidikan agama islam masa pandemi covid-19.